Differences between multi-triggered and single-triggered food anaphylaxis in children: a real life study - Şule Büyük Yaytokgil; İlknur Külhaş Çelik; Zeynep Şengül Emeksiz; Betül Karaatmaca; Tayfur Giniş; Selma Alim Aydın; Müge Toyran; Emine Dibek Mısırlıoğlu; Ersoy Civelek (The Turkish Journal of Pediatrics, 2025)
Background. Food-induced anaphylaxis (FIA) is a severe form of food allergy, and literature data about multi-triggered FIA is scarce. This study aimed to evaluate the differences between multi-triggered and single-triggered food anaphylaxis in children.